Clinical efficacy and safety of removing blood stasis and resolving phlegm in the treatment of epilepsy with cognitive impairment: A systematic review and meta-analysis. Issue 37 (16th September 2022) - Yu, Yang Yang; Yuan, Can Xing; Gu, Chao
Abstract : Backgrounds: Epilepsy is a chronic encephalopathy caused by abnormal discharge of neurons in the brain, resulting in brain dysfunction. Cognitive impairment is one of the most common complications of epilepsy. The current treatment of epilepsy in the control of symptoms at the same time cause a lot of side effects, especially the aggravation of cognitive impairment. Many literatures have stated that the efficacy and safety of integrated Traditional Chinese and western medicine in the treatment of epilepsy with cognitive impairment is superior to that of western medicine alone. In this systematic review and meta-analysis, we intend to evaluate the clinical efficacy and safety of removing stasis and resolving phlegm in the treatment of epilepsy with cognitive impairment. Objective: To systematically evaluate the clinical efficacy and safety of removing blood stasis and resolving phlegm in the treatment of epilepsy with cognitive impairment. Methods: The Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) guidelines were followed to conduct this systematic review. The Chinese Journal Full Text Database (CNKI), Wanfang Database, CQVIP Database (CQVIP), Cochrane Library, EMbase, and Pubmed were searched by computer, and randomized controlled studies on the efficacy of removing blood stasis and resolving phlegm in the treatment of epilepsy with cognitive disorders were included. Retrieval was carried out until January 2022, and relevant data were extracted for meta-analysis using Rev Man5.3 software. Results: Fourteen randomized controlled studies with a total of 1198 patients were included, including 601 patients in the control group and 597 patients in the treatment group (experimental group). Results: Meta-analysis results showed that compared with the treatment of epilepsy with cognitive impairment in the western anti-epileptic drugs group alone, the treatment of epilepsy with cognitive impairment combined with the method of removing blood stasis and resolving phlegm could significantly improve the clinical efficacy of epilepsy (OR = 3.41, 95% CI 2.39–4.88, P  < .001). Improved the TCM symptom score (OR = 3.99, 95% CI 1.72–9.26, P  < .001). Increased the EEG improvement rate (RR = 1.39, 95% CI 1.05–1.84, P  = .02). Improved MOCA score and cognitive function (MD = 3.54, 95% CI 1.68–5.40, P  < .001). Improved QOLIE-31 cognitive function score. Improved cognitive function (MD = 7.22, 95% CI 3.35–11.08, P  < .001). Improved the incidence of adverse reactions (RR = 0.50, 95% CI 0.33–0.76, P  = .001). Conclusion: Compared with the treatment of epilepsy with cognitive impairment by western anti-epileptic drugs alone, the treatment of epilepsy with cognitive impairment combined with the method of removing blood stasis and resolving phlegm is superior to the treatment of epilepsy with cognitive impairment by western anti-epileptic drugs alone.